Dietary supplementation of Rosmarinus officinalis L. leaves in sheep affects the abundance of rumen methanogens and other microbial populations. Issue 1 (December 2016) - Cobellis, Gabriella; Yu, Zhongtang; Forte, Claudio; Acuti, Gabriele; Trabalza-Marinucci, Massimo
Abstract Background Rumen microbiome has a great influence on ruminant health and productivity. Different plant extracts have been tested for their ability to modulate the rumen microbiome to improve feed digestion and fermentation. Among the evaluated plant extracts, essential oils, tannins, and saponins appeared to have positive effects on rumen protein metabolism, volatile fatty acids production, and methane and ammonia production. Methods The objective of this study was to evaluate the effect of rosemary (Rosmarinus officinalis L. ) leaves and essential oils on rumen microbial populations. Four ruminally cannulated sheep were used in a 4×4 Latin square design fed (21 d/period): 1) a control diet composed of alfalfa hay and concentrate pellet (CTR), 2) CTR supplemented with 7 g/d/sheep of rosemary essential oil adsorbed on an inert support (EO), 3) CTR with 10 g/d/sheep of dried and ground rosemary leaves (RL), and 4) CTR with 10 g/d of dried and ground rosemary leaves pelleted into concentrate (RL pellet). Abundance of total bacteria, archaea, protozoa, and some select bacterial species or groups was quantified using qPCR, while the community of bacteria and archaea was profiled using denaturing gradient gel electrophoresis. Results No difference in abundance was noted for total bacteria, protozoa, orRuminococcus flavefaciens between the control and the treatments, but the rosemary leaves, either in loose form or in pellet, decreased the abundance of archaea and the genusPrevotella (P < 0.001). The rosemary leaves in loose form also decreased (P < 0.001) the abundance ofRuminococcus albus andClostridium aminophilum, while the EO increased (P < 0.001) the abundance ofFibrobacter succinogenes. The community of bacteria and archaea was not affected by any of the supplements. Conclusions Being able to affect the abundance of several groups of rumen microbes that are known to be involved in degradation of protein and fiber and production of methane and ammonia, rosemary leaves may be used to modulate rumen microbiome and its function.